Look up, look out campaign - Chia, Cherilyn Guat Joo (2015)
Look Up, Look Out is a campaign about distracted walking, with a focus on road safety. It is a social movement started by four undergraduates from Nanyang Technological University, Wee Kim Wee School of Communication and Information, with the intention of encouraging youth not to use their mobile devices while crossing the roads. The campaign is the first road safety campaign targeted at pedestrians, where previous efforts on distracted commuting focused mainly on drivers. The campaign targets youth aged 17 to 25, as it was found that young people around this age group had the highest smartphone penetration rates, coupled with the highest weekly instant-message and social networking usage on smartphones. These reasons also influenced the platforms chosen to reach out to them, primarily through social media – Facebook and Instagram. Face-to-face interactions with the target audience were not missed out, with roadshows in schools forming the bulk of our on-ground efforts. This report provides a background to the issue of distracted walking, followed by the group’s primary research involving over 400 youth in the target age group. This research shaped the campaign’s main strategy of “Show, Don’t Tell”, along with the messaging and tactics employed. Successes, challenges, limitations and recommendations are also explored as part of the post-campaign evaluation. This evaluation provides an avenue for discussion, and may form the basis for future projects of the same thread. The appendix at the end of the paper also includes original communication materials, such as documents, collateral and diagrams for reference.